Implementation of Interactive Science Module Based on Problem Based Learning to Increase Activeness Study - Rufia, Rufia; Misnah, Misnah; Ratu, Bau (Journal of Education Method and Learning Strategy, 2025)
This study aims to determine the effectiveness of the implementation of interactive modules of Science based on Problem Based Learning (PBL) in improving the learning activity and achievement of fourth-grade students of SDN 09 Bungku. The research methods used were observation, interviews, and evaluation of student learning outcomes before and after implementing the module. The results showed that the implementation of interactive modules based on PBL significantly improved student learning activity. Students became more enthusiastic, actively discussed, asked questions, and solved problems independently or in groups. In addition, student learning achievement also experienced a significant increase, with all students achieving the Minimum Completion Criteria (KKM). This interactive module provides an enjoyable and meaningful learning experience by presenting contextual materials, visual illustrations, and interactive activities that stimulate critical thinking and student creativity. The teacher acts as a facilitator who guides students in using the module to make the learning process more effective and structured. This study recommends the use of interactive modules based on PBL as an alternative innovative learning that can improve motivation, involvement, and student learning outcomes in elementary schools.